2017
DOI: 10.1007/978-3-319-57532-2_12
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in Arctic Socio-economic Scenarios

Abstract: Scenarios are neither predictions nor forecasts, but explore a range of possible futures. Socio-economic scenarios enable the consideration of different uncertainties related to the future and may improve decision-making by enabling the development and analysis of robust decisions. The development of socioeconomic scenarios in the Arctic has been a fairly popular topic for scenario analyses. This study reviews ten selected socio-economic scenarios developed for the Arctic region that differ in structure and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Methodologically, many scenario exercises focus on two key drivers of change to develop four explorative scenarios. A review of published Arctic socio-economic scenarios showed that they almost always included climate change as one tier and governance or management of natural resources as the second tier, with a shift in recent years towards political factors (Haavisto, Pilli-Sihvola, & Harjanne, 2017). Such a two-dimensional approach comes with important limitations.…”
Section: Multiple Dimensions and Risks Of False Dichotomiesmentioning
confidence: 99%
“…Methodologically, many scenario exercises focus on two key drivers of change to develop four explorative scenarios. A review of published Arctic socio-economic scenarios showed that they almost always included climate change as one tier and governance or management of natural resources as the second tier, with a shift in recent years towards political factors (Haavisto, Pilli-Sihvola, & Harjanne, 2017). Such a two-dimensional approach comes with important limitations.…”
Section: Multiple Dimensions and Risks Of False Dichotomiesmentioning
confidence: 99%
“…In addition, the improvement of Arctic weather and sea ice forecasting services has gained a lot of attention since the Year of Polar Prediction 41 . The strong seasonal and inter-annual sea ice variability around Svalbard in parallel with increasing maritime activities has a demand-pull effect on achieving the need for accurate and reliable sea ice services 42 , 43 . End-users operating around Svalbard emphasize the need for publicly accessible ice charts to be available daily, even more so when sailing in the north and east of the archipelago.…”
Section: Discussionmentioning
confidence: 99%